Adipokinetic hormone exerts its anti-oxidative effects using a conserved signal-transduction mechanism involving both PKC and cAMP by mobilizing extra- and intracellular Ca2+ stores - Bednářová, Andrea; Kodrík, Dalibor; Krishnan, Natraj (Comparative biochemistry and physiology. Toxicology & pharmacology, 2013)
The involvement of members of the adipokinetic hormone (AKH) family in regulation of response to oxidative stress (OS) has been reported recently. However, despite these neuropeptides being the best studied family of insect hormones, their precise signaling pathways in their OS responsive role remain to be elucidated. In this study, we have used an in vitro assay to determine the importance of extra and intra-cellular Ca(2+) stores as well as the involvement of protein kinase C (PKC) and cyclic adenosine 3',5'-monophosphate (cAMP) pathways by which AKH exerts its anti-oxidative effects. Lipid peroxidation product (4-HNE) was significantly enhanced and membrane fluidity reduced in microsomal fractions of isolated brains (CNS) of Pyrrhocoris apterus when treated with hydrogen peroxide (H2O2), whereas these biomarkers of OS were reduced to control levels when H2O2 was co-treated with Pyrap-AKH. The effects of mitigation of OS in isolated CNS by AKH were negated when these treatments were conducted in the presence of Ca(2+) channel inhibitors (CdCl2 and thapsigargin). Presence of either bisindolylmaliemide or chelyrythrine chloride (inhibitors of PKC) in the incubating medium also compromised the anti-oxidative function of AKH. However, supplementing the medium with either phorbol myristate acetate (PMA, an activator of PKC) or forskolin (an activator of cAMP) restored the protective effects of exogenous AKH treatment by reducing 4-HNE levels and increasing membrane fluidity to control levels. Taken together, our results strongly implicate the importance of both PKC and cAMP pathways in AKHs' anti-oxidative action by mobilizing both extra and intra-cellular stores of Ca(2+).
Keywords: oxidační stres; tetradekanoylforbolacetát; Calcium channel; Calcium; Tetradecanoylphorbol Acetate; Cell signaling; Hydrogen peroxide; AMP cyklický; Oxidative stress; cyclic adenosine monophosphate; Cyclic AMP; vápník; signální transdukce; hmyzí hormony; cAMP; PKC; blokátory kalciových kanálů; proteinkinasa C; Aldehydes; Signal Transduction; Oligopeptides; 4-HNE; Membrane fluidity; adipokinetic hormone; kyselina pyrrolidonkarboxylová; aldehydy; Pyrrolidonecarboxylic Acid; Protein kinase; Adipokinetic hormone; Animals; Calcium Channel Blockers; fluidita membrány; AKH; zvířata; Insect Hormones; peroxidace lipidů; protein kinase C; Membrane Fluidity; Lipid Peroxidation; Oxidative Stress; oligopeptidy; Heteroptera; Protein Kinase C; 4-hydroxy-2-nonenal